A systematic review of adherence to physical activity interventions in individuals with type 2 diabetes. Issue 8 (26th March 2021) - MacDonald, Christopher S.; Ried‐Larsen, Mathias; Soleimani, Jalal; Alsawas, Mouaz; Lieberman, Daniel E.; Ismail, Abdalla S.; Serafim, Laura P.; Yang, Ting; Prokop, Larry; Joyner, Michael; Murad, Mohammad Hassan; Barwise, Amelia
Abstract: Lifestyle interventions are pivotal for successful management of type 2 diabetes (T2D), however, the proportion of people with T2D adhering to physical activity advice has not been thoroughly studied. The purpose of this systematic review was to summarise the evidence on adherence to exercise or physical activity components in lifestyle interventions in those with T2D. We searched MEDLINE EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and Scopus on 12 November 2019. Eligible studies enrolled adults with T2D and reported the proportion of adherence to lifestyle interventions as a primary or secondary outcome. We included 11 studies (nine randomised controlled trials (RCTs) enrolling 1717 patients and two nonrandomised studies enrolling 62 patients). Only one of the studies had low risk of bias. The proportion of participants adhering to physical activity varied from 32% to 100% with a median of 58%. Adherence was higher in interventions using supervised training and lowest in interventions using remote coaching and the adherence rate in observational studies was higher compared to RCTs (92% vs. 55%; p < 0.01). Study duration, risk of bias, or participants' sex, were not associated with adherence to physical activity. The proportion of those with T2D adhering to physical activity interventions for T2D varies widely and most of the included studies had a high risk of bias. These findings have important implications for planning and power analysis of future trials and when counselling patients about lifestyle interventions including physical activity or exercise components.